Presentation of an Outsourcing Model of Marketing Activities of Academic Sport Events - Rahim Shirazinejad; Ahmad Torkfar; Mohammad Sadegh Afroozeh; Hamidreza Safari Jafarloo; Maryam Ghodsi (Universidad de Antioquia, 2021)
Introduction: The objective of this study was presenting a model of outsourcing marketing activities of academic sport events. Material and Methods: The present study is a mixed research that is done through qualitative and quantitative methods. The statistical population of this study includes all experts in the field of academic sport and marketing in Iran at public, Islamic Azad, Payame Noor and Elmi Karbordi, universities. The research instruments were a questionnaire and an interview. In the quantitative analysis part of the research, the interpretive structural modeling method and the structural equations with PLS approach are used. Results and Discussion: The qualitative results of the research showed that 41 attributes were extracted from the interviews which were classified into 6 categories of strategic, managerial, motivational, sport, technical and legal factors. The results showed that among the identified factors, legal and technical factors have an underlying role in the formation of other factors for the development of outsourcing marketing activities of academic sport events. Conclusion: This issue highlighted the importance of legal and technical factors for the development of outsourcing solutions for academic sports events marketing activities.